1997
DOI: 10.1128/aac.41.4.818
|View full text |Cite
|
Sign up to set email alerts
|

An axenic amastigote system for drug screening

Abstract: Currently available primary screens for selection of candidate antileishmanial compounds are not ideal. The choices include screens that are designed to closely reflect the situation in vivo but are labor-intensive and expensive (intracellular amastigotes and animal models) and screens that are designed to facilitate rapid testing of a large number of drugs but do not use the clinically relevant parasite stage (promastigote model). The advent of successful in vitro culture of axenic amastigotes permits the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(68 citation statements)
references
References 73 publications
6
56
0
1
Order By: Relevance
“…Remarkably, the IC 50 to AmB of all primary isolates varied very little between strains, with karyotypes having IC 50 values ranging from 0.26 to 0.6 mg/mL. Similar IC 50 values were observed between promastigotes and amastigotes, further supporting the idea that the stage of the parasite does not seem to influenc AmB susceptibility [40,41]. One of the most important finding of this study is that parasites that have been in contact with AmB for many episodes are not less susceptible to the drug than are primary isolates (table 1).…”
Section: Discussionsupporting
confidence: 74%
“…Remarkably, the IC 50 to AmB of all primary isolates varied very little between strains, with karyotypes having IC 50 values ranging from 0.26 to 0.6 mg/mL. Similar IC 50 values were observed between promastigotes and amastigotes, further supporting the idea that the stage of the parasite does not seem to influenc AmB susceptibility [40,41]. One of the most important finding of this study is that parasites that have been in contact with AmB for many episodes are not less susceptible to the drug than are primary isolates (table 1).…”
Section: Discussionsupporting
confidence: 74%
“…Several studies [11][12][13][14] have found that Sb(V) is inefficient against amastigotic Leishmania parasites cultured axenically, whereas it has effect on parasites when intracellular; this may indicate that the macrophages are the primary site for activation of the Sb drug. Shaked-Mishan [17] found reduction of Sb(V) within the parasite which could explain that other authors have reported on axenically amastigotes where Sb(V) did show activity [15,16]. Different parasite strains is likely an explanation of these discrepancies, but even for 'self-reducing' strains, a reduction in the macrophages will most likely contribute significantly to the Sb(V) drugs' effect in the clinical situation, as the parasite will take up Sb(III) if present (except for certain Sb-resistant strains) [9,17].…”
Section: Resultsmentioning
confidence: 92%
“…The differences in sensibility of promastigotes compared to amastigotes is well documented (Callahan et al, 1997;Berman et al, 1982;Croft et al, 1981). Callahan et al (1997) and us herein showed that Amphotericin B did have an activity on promastigotes of Leishmania mexicana equivalent to the one on axenic amastigotes (IC 50 around 0.2 g/ml). On the contrary, Glucantime was shown to be almost inactive on promastigotes (IC 50 : 1100 g/ml) but active on amastigotes (IC 50 : 30 g/ml).…”
Section: Discussionmentioning
confidence: 76%